A Meta-Analysis of the Bacterial and Archaeal Diversity Observed in Wetland Soils - Xiaofei Lv; Junbao Yu; Yuqin Fu; Bin Ma; Fanzhu Qu; Kai Ning; Huifeng Wu (The Scientific World Journal)
This study examined the bacterial and archaeal diversity from a worldwide range of wetlands soils and sediments using a meta-analysis approach. All available 16S rRNA gene sequences recovered from wetlands in public databases were retrieved. In November 2012, a total of 12677 bacterial and 1747 archaeal sequences were collected in GenBank. All the bacterial sequences were assigned into 6383 operational taxonomic units (OTUs 0.03), representing 31 known bacterial phyla, predominant with Proteobacteria (2791 OTUs), Bacteroidetes (868 OTUs), Acidobacteria (731 OTUs), Firmicutes (540 OTUs), and Actinobacteria (418 OTUs). The genus Flavobacterium (11.6% of bacterial sequences) was the dominate bacteria in wetlands, followed by Gp1, Nitrosospira, and Nitrosomonas. Archaeal sequences were assigned to 521 OTUs from phyla Euryarchaeota and Crenarchaeota. The dominating archaeal genera were Fervidicoccus and Methanosaeta. Rarefaction analysis indicated that approximately 40% of bacterial and 83% of archaeal diversity in wetland soils and sediments have been presented. Our results should be significant for well-understanding the microbial diversity involved in worldwide wetlands.